Alternate Degree Program Delivery Formats for Adult Students: What is Lost and What is Gained? - Carrie J. Boden; W. Franklin Spikes (Adult Education Research Conference, 2009)
A growing number of adult learners are turning to accelerated degree programs to complete an initial or more advanced college degree. While various aspects of these types of degree programs have been discussed in the literature, relatively little is known about how the epistemological beliefs as well as the self-directed learning readiness of adults who are enrolled in accelerated degree programs change over time. A discussion of the findings of recent research about the relationship and the development of these phenomena by adult learners along with implications for improved adult education form the basis for this research roundtable.